23rd AIAA/CEAS Aeroacoustics Conference 2017
DOI: 10.2514/6.2017-4173
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of noise reduction mechanisms of serrated trailing edges under zero lift condition

Abstract: The relation between the far-field noise and the flow field, in presence of serrated and combed-serrated trailing edge, is studied to explain the associated noise reduction mechanisms. Both serration geometries are retrofitted to a NACA 0018 wing. Computations are carried out by solving the fully explicit, transient, compressible Lattice Boltzmann equation, while the acoustic far-field is obtained by means of the Ffowcs-Williams and Hawking integral solution. A link between the far-field noise and the relevant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…The funneling effect is also evident from the contours of time averaged streamwise velocity component at the serration surface that show the flow approaching the serrations seeping into the serration gaps. This observation has later been verified by a numerical study in 15 , where simulations on a serrated NACA 0018 aerofoil under zero lift conditions have shown that the near-wall (z = 0.5 mm from the wall) spatial distribution of time averaged mean streamwise velocity component has shown an increase when moving away from the root towards the tip, indicating an acceleration of the flow.…”
Section: Introductionmentioning
confidence: 60%
“…The funneling effect is also evident from the contours of time averaged streamwise velocity component at the serration surface that show the flow approaching the serrations seeping into the serration gaps. This observation has later been verified by a numerical study in 15 , where simulations on a serrated NACA 0018 aerofoil under zero lift conditions have shown that the near-wall (z = 0.5 mm from the wall) spatial distribution of time averaged mean streamwise velocity component has shown an increase when moving away from the root towards the tip, indicating an acceleration of the flow.…”
Section: Introductionmentioning
confidence: 60%
“…This effect is also evident from the contours of time averaged u (streamwise) velocity component at the serration surface that show the flow approaching the serrations seeping into the serration gaps. This observation has later been verified by a numerical study in [14], where in case of a serrated NACA0018 aerofoil under zero lift conditions, the near-wall (y=0.5mm from the wall) spatial distribution W of time averaged mean velocity u (streamwise) component has shown an increase moving away from the root towards the tip, indicating an acceleration of the flow.…”
Section: Introductionmentioning
confidence: 58%
“…In addition, at all the Reynolds number, the noise levels in the upstream are found to be higher compared to the downstream for both the airfoils indicating that directivity of the acoustic sources is dominant towards the upstream. 36 Figure 16 shows the directivity pattern at Reynolds number of 3.0 Â 10 5 at angles of attack of 0 , 2 , and 4 . At this Reynolds number, the noise emissions from airfoil with holes are larger compared to the reference airfoil at angles of attack of 0 and 2 , and the noise dominance is observed at the upstream angle of around 130 .…”
Section: Directivity Studiesmentioning
confidence: 99%